Incidence and mortality of brain abscess in Denmark: a nationwide population-based study. (January 2020) - Bodilsen, J.; Dalager-Pedersen, M.; van de Beek, D.; Brouwer, M.C.; Nielsen, H.
Abstract: Objectives: To examine the incidence and mortality of brain abscesses. Methods: We accessed nationwide population-based medical registries to obtain data for patients with first-time brain abscesses in Denmark from 1982 through 2016. Annual age- and sex-standardized incidence rates with 95% confidence intervals were calculated and compared by direct standardization. We used Cox regression to compute mortality rate ratios adjusted for age and year groups, sex and Charlson comorbidity index score. Results: We identified 1384 patients (37% female). The overall standardized incidence rate of brain abscess was 0.76 per 100 000 person-years (95% confidence interval 0.70–0.81). The incidence rates gradually increased from 0.60 during 1982–88 to 0.90 per 100 000 person-years during 2010–16, yielding an incidence rate ratio of 1.50 (95% confidence interval 1.26–1.79). This increase in incidence was most pronounced in the proportions of brain abscess patients >40 years of age and those with immuno-compromise. The 1-year mortality declined from 29% during 1982–88 to 20% during 2010–16, yielding an adjusted mortality rate ratio of 0.44 (95% confidence interval 0.31–0.63). Risk factors for death were advanced age, Charlson comorbidity index >0, immuno-compromised status and congenital heart disease. Conclusions: The incidence of brain abscess in Denmark is low but increasing, especially in the elderly, along with an increasing proportion of brain abscess patients with immuno-compromise. The prognosis has improved during the last decades, but mortality remains high. Risk factors for death in our study were advanced age, presence of comorbidity, immuno-compromised status and congenital heart disease.